Urgensi implementasi smart tourism untuk kemajuan pariwisata Indonesia - Hendi Prasetyo; Muhammad Bachtiar Rifai (STIE Pariwisata API Yogyakarta, 2022)
In order to advance Indonesian tourism, it is necessary to implement smart tourism. The purpose of this study is to describe the urgency of implementing smart tourism for the advancement of Indonesian tourism. This research is qualitative research with descriptive analysis and using literature study data collection techniques. The results of the research that has been carried out show that the existence of smart tourism is basically an effort to meet the needs of tourists by combining information technology devices. Tourists currently need travel application facilities in order to facilitate travel and determine tourism activities from the information provided so that tourists can access them when they need them. The application of the smart tourism concept will be the development of innovation between technology and tourist information needs. Optimizing the utilization of all the potential and resources owned will encourage an increase in the tourist experience of tourism activities. The development of the smart tourism concept will also always coexist with technological advances so it requires continuous innovation in order to achieve the expected goals. Based on the research that has been done, it can be concluded that the concept of smart tourism is able to provide tourism experiences and services by utilizing technological advances from stakeholders (government, destination managers, local communities, and tourists) who utilize information and communication technology.